Pedagogical Implications of Gha͂tu Folk Dance in EFL Classes - Gurung, Raj Kumar (Journal of NELTA Gandaki, 2022)
This paper proposes teaching Gha͂tu folk dance as a performing art in EFL classes for effective teaching and learning activities. Like dance performance, language skills are also performing arts. The study examines the English language proficiency of intermediate students in general. Their performance is not as satisfactory as expected. One major finding of the study is that the relationship between teachers and students and students to students is not harmonious. Gha͂tu can play a catalytic role in maintaining the relations between teachers and learners. This cultural activity is the source of good human relations, good coordination, patience, group work, devotion, submissiveness and many more. This article explores how this cultural activity enhances the teaching-learning activities in EFL classes, what factors are affecting students’ performance, and how Gha͂tu inspires teaching-learning pedagogies. But it has not been studied from this perspective yet. So, Gha͂tu is to be introduced in the syllabus. The study employs the human relations theory to interpret and analyze this Gha͂tu cite and relate it to this research. Teaching Gha͂tu folk dance in EFL classes can create an exciting environment as it is a new teaching pedagogy. This makes all the students actively participate in teaching-learning activities. Gha͂tu can make classroom activities effective, active, and interactive if it is introduced in the syllabus. The active participation of both language and literature students enhances the English language proficiency in EFL classes.